An investigation on the factor that effect non-performing loan in Malaysia towards macroeconomic variables / Muhamad Syahlan Baharin - Baharin, Muhamad Syahlan (Faculty of Business and Management, 2011)
This paper studies empirically the movement of Nonperforming Loan (NPL) in Malaysia. The timing of research taken was in range of 5 years makes use of quarterly data ranged from January 2006 to December 2010. The study will be used multiple regression method to see the relationships between dependent and independent variables. The dependent variable of the study is the NPL. The independent variables were selected and identified namely as Gross Domestic Product (GDP), Base Lending Rate (BLR) and Unemployment Rate (UR). The economic will reflect the NPL at Malaysia whether to increase or decrease. The performance may be influence by many factors, relation with macroeconomics and others. It may be cause by GDP, BLR and UR. According to the overall results in this study it indicates the most independent variables are the most give an impact to the NPL at Malaysia. It shows a significance relationship between the variables. The relationship implies that GDP and UR are negatively related to NPL and BLR is positively related with the NPL consistent with the previous research done before. The result of this research will be very useful for other researchers and banking institution that aware about the movement of NPL at Malaysia.